2018
DOI: 10.1016/j.ijantimicag.2018.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of methicillin-resistant and susceptible coagulase-negative staphylococci in milk from cows with clinical mastitis in Tunisia.

Abstract: Coagulase-negative staphylococci containing a diversity of antimicrobial resistance genes are frequently detected in milk of mastitis cows. This fact emphasizes the importance of identifying CNS when an intramammary infection is present because of the potential risk of lateral transfer of resistant genes among staphylococcal species and other pathogenic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 37 publications
7
40
0
1
Order By: Relevance
“…samples, Klibi et al, using SCCmec typing, discovered methicillin-resistant S. epidermidis possessed SCCmec type-Iva. 41 The isolates also possessed the recombinase genes ccr A2/B2-class B mec gene complex determined by PCR of the ccr recombinases (1-5). Also, Ehlers et al found that SCCmec type IV was the most predominant with 31% of S. epidermidis isolates belonging to that class.…”
Section: Typing Methods For Consmentioning
confidence: 99%
See 4 more Smart Citations
“…samples, Klibi et al, using SCCmec typing, discovered methicillin-resistant S. epidermidis possessed SCCmec type-Iva. 41 The isolates also possessed the recombinase genes ccr A2/B2-class B mec gene complex determined by PCR of the ccr recombinases (1-5). Also, Ehlers et al found that SCCmec type IV was the most predominant with 31% of S. epidermidis isolates belonging to that class.…”
Section: Typing Methods For Consmentioning
confidence: 99%
“…In comparison to MR-CoNS, the MS-CoNS isolates showed lower levels of resistance to antibiotics. 41 This was expected, as methicillin resistance is known to cause cross resistance to other antibiotics. 103 Dhaouadi et al however, reported the first occurrence of mecC gene in CoNS (S. sciuri) in Africa (having been already reported in animals in Europe), 104 obtained from cows and manure, in a study which also found the ARGs tet(K), mecA, msr(A), blaZ, erm(A), and erm(B) simultaneously from cow (milk), manure, and human (nares) sources, which may be suggestive of an exchange of ARGs among these sources.…”
Section: Occurrence Role and Antibiotic Susceptibility Of Suspectedmentioning
confidence: 96%
See 3 more Smart Citations